IMPLEMENTATION OF E-GOVERNMENT AS A PUBLIC SERVICE IN WARINGINSARI TIMUR VILLAGE - Lailatul Istikomah; Rinawati Rinawati; Desi Handayani (STMIK Pringsewu Lampung, 2018)
Based on the results of the Indonesian e-government rating (PeGI) at the provincial level at the end of 2015, Lampung province received the title of 17 out of 20 under the category of less. E-government for government institutions is useful to improve the quality of public services in providing information to the public, improving relations between government, community empowerment and implementing a more efficient government. Waringinsari Timur Village is a village that needs to be answered by government agencies in carrying out its functions, namely improving the quality of public services and a wealth of potential villages that are income-generating such as livestock, plantations, agriculture, small industries / homes. Researchers conducted a study by building a website application with the theme